INTEGRATED ENTREPRENEURSHIP EDUCATION, ENTREPRENEURSHIP INTENTION AND MULTIDIMENSIONAL POVERTY ALLEVIATION IN WEST JAKARTA - Amran, Ellyana (Universitas Mataram, 2023)
Poverty cannot be handled by individuals alone; they must work together with the government, society, and the state. Entrepreneurship is believed to be the driving force of the economy, opening up and creating job opportunities as a solution to poverty alleviation. The aims of this study were to describe the effect of integrated entrepreneurship education on the multidimensional poverty alleviation of housewives in the Krendang area, West Jakarta, mediated by entrepreneurship intention. This area is a densely populated area in Southeast Asia with various limited facilities, located very strategically in a business location. This study uses qualitative and quantitative analysis with a sample of 75 respondents, taken by a purposive sampling technique. The data has been collected and processed using the Structural Equation Model methodology. The findings of this study are, integrated entrepreneurship education has a positive effect on multidimensional poverty alleviation; integrated entrepreneurship education has a positive effect on entrepreneurship intention; entrepreneurship intention has a positive effect on multidimensional poverty alleviation; and integrated entrepreneurship education has a positive effect on multidimensional poverty alleviation indirectly through entrepreneurship intention.